2021
DOI: 10.26451/abc.08.04.05.2021
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Crowd Size, Composition, and Noise Level On Pool Use in a Mixed-Species Penguin Colony

Abstract: Studies on how visitors affect penguins in human care report a mixture of negative, neutral, and positive impacts on behavior and physiology. Swimming is a highly motivated behavior that may promote positive welfare in penguins. We investigated how visitor crowd size, composition, and noise levels impact pool use in a mixed-species colony housing king (Aptenodytes patagonicus; n = 20), gentoo (Pygoscelis papua; n = 14), and southern rockhopper (Eudyptes chrysocome; n = 24) penguins. We used video and sound log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Many studies of visitor impacts on zoo animal behavior, even within the same species, have found contradictory results (Birke, 2002; Choo et al, 2011; Hashmi & Sullivan, 2020), and increasingly evidence suggests human presence may not be the largest predictor of animal behavior in zoos or aquariums (Edes et al, 2021; Rose et al, 2020). This is consistent with our findings, as even in cases where nonlinear models were the most supported by the data, their predictive strength was relatively weak in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of visitor impacts on zoo animal behavior, even within the same species, have found contradictory results (Birke, 2002; Choo et al, 2011; Hashmi & Sullivan, 2020), and increasingly evidence suggests human presence may not be the largest predictor of animal behavior in zoos or aquariums (Edes et al, 2021; Rose et al, 2020). This is consistent with our findings, as even in cases where nonlinear models were the most supported by the data, their predictive strength was relatively weak in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not systematically assess visitor numbers, we observed the penguins in both habitats during periods when they were closed to visitors, and swimming patterns remained unchanged. Similarly, Edes et al [12] found no relationship between pool use and crowd size, crowd composition, or noise levels in king penguins living in another mixed-species zoo colony. Crowd size did not affect the pool use of captive Humboldt penguins, either [39].…”
Section: Changes In Aquatic Behaviorsmentioning
confidence: 95%
“…Despite the popularity and charismatic nature of penguins, studies of their welfare were rare until recent years, with existing research focusing primarily on visitor effects [9][10][11][12][13][14][15][16]. Pool use has been a primary focus of other studies.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the presence of human visitors increased distress levels of wolves (Canis lupus) (Pifarré et al, 2012), pandas (Ailuropoda melanoleuca) (Quadros et al, 2014), orangutans (Pongo pygmaeus) (Birke, 2002), and koalas (Phascolarctos cinereus) (Larsen et al, 2014). The way animals use their enclosures can also be affected by the presence and location of humans visitors as shown with various penguins species (Chiew et al, 2020;Edes et al, 2021) and flamingos (Phoenicopterus roseus and Phoenicopterus chilensis) (Rose et al, 2021). According to Hosey, factors such as the temperament of a species or an individual, the presentation of the animals, and the behavior of the visitors when interacting with the animals determine whether zoo visitors have stressful effects on animals.…”
Section: Human-animal Relationship (Har) As Enrichmentmentioning
confidence: 99%